(untitled) (Docentes 2.0 Journal, 2020)
This action research was conducted with the aim of analyzing the influence of the Interactive Model of Keith E. Stanovich in the students’ reading comprehension of short texts in English. The previously mentioned reading model takes into account the continuous interaction between the bottom-up model in which the reader decodes a text starting from the smallest units (letters to words, phrases to sentences, etc.) and top-down model in which the reader contributes a great deal of knowledge, expectations, assumptions and questions to the text and, giving a basic understanding of the vocabulary, continues reading while the text confirms his expectations. Thus, text comprehension can be understood as an interactive process between the reader’s prior knowledge of content and structure, and the text itself. This study was developed under a mixed approach and the instruments employed to gather the data were two diagnostic tests, four workshops, and two final tests applied to ten ninth-grade students from the Normal School in San Mateo (Boyacá). The data were analyzed quantitatively and qualitatively, using the proposed research instruments by Vanegas (2020). Regarding the findings, it was concluded that the use of the interactive reading approach was effective in improving students’ reading comprehension ability both literally and inferentially.